Delving Into the Working Mechanism of Prediction in Sentence Comprehension: An ERP Study - Huang, Yunlong; Jiang, Minghu; Guo, Qian; Wang, Yuling (Frontiers in Psychology, 2021)
The present study aims to delineate the working mechanism of prediction in sentence comprehension, by disentangling the influence of the facilitated general memory retrieval from the coexistent influence of the predicted language-specific semantic and/or syntactic information for the first time. The results support that prediction might influence the downstream cognitive processing in two aspects: 1) the pre-activated information facilitate the retrieval of a matched input in memory and, 2) the pre-activated information interacts with higher-level semantic/syntactic processing. More importantly, the present findings suggest that these two types of influences seem to occur at different stages of sentence comprehension: the facilitated memory retrieval of the input modulates N400 amplitude and the latency of post-N400 late central-parietal positivity/P600, while the predicted semantic/syntactic information and/or their interactions modulates the amplitude of the late positivity. The present findings would be helpful for interpreting the underlying mechanism of observed effects in prediction studies.